The role of international research agencies in strengthening forest research in Africa - Sayer, Jeffrey A.; Ng, F.S.P.; Palmer, J.R. (1995)
Among the range of problems requiring research, some are most relevant for particular countries and require special local knowledge or facilities for research. Others are common to eco-regions or ecosystems which span several countries; for these, a regional approach through networked research groups may be more efficient and effective. CIFOR has identified a set of strategic problems, through surveys of demands, which involve research leading to generalizable results, adaptable to local situations. CIFOR will work through institution-strengthening associations with national partners towards resolution of these strategic problems.